Induction of cystic ovarian follicles (COFs) in cattle by using an intrafollicular injection of indomethacin - Rebecca LAPP; Volker RÖTTGEN; Torsten VIERGUTZ; Joachim M. WEITZEL; Andreas VERNUNFT (The Society for Reproduction and Development, 2020)
The aim of this study was to establish a model to induce cystic ovarian follicles (COFs) in cattle using the cyclooxygenase inhibitor, indomethacin. Eighteen Holstein-Frisian cattle were synchronized with prostaglandin F2alpha (PGF2α) and gonadotropin-releasing hormone (GnRH). Ultrasound-guided transvaginal intrafollicular injections were performed in 23 preovulatory follicles with different concentrations of indomethacin 16 h after GnRH administration. An injection of 0.2 ml 35 µM indomethacin solution (resulting in a final concentration of 8 µg/ml in the follicular fluid) was the minimal dosage leading to COF formation. The induced COFs reached a maximum mean diameter of 36.9 ± 4.5 mm eleven days after injection. The estrous cycle was extended to 25-39 days. Luteinization was first observed 4 days after injection, accompanied by a slight increase in plasma progesterone concentration. The bioactivity of indomethacin was demonstrated by the decrease of prostaglandin E2 in the follicular fluid of three animals. The method presented here is minimally invasive and allows for the generation of defined COFs for further investigations.